ANALISIS STRATEGI KOMUNIKASI DALAM SOSIALISASI PROGRAM KARTU IDENTITAS ANAK - Layung Paramesti Martha; Irma Suci Adiyasa (UNIVERSITAS PAKUAN, 2022)
This study aims to analyse how the communication strategy is applied in socializing the Child Identity Card program. The study was conducted at the Population and Civil Registry Office of Bogor Regency and Cibinong District Region. This research method uses a qualitative descriptive study using two concepts, namely the communication strategy concept of R. Wayne, et al in Effendy and communication strategy barriers Ruslan. The results of this study note that the communication strategy step adopted pays attention to all components in communication. Even so, the results of the study showed that the socialization of the Childrens Identity Card program was still included in the Dukcapil program of the Indonesian Movement to be Aware of Population Administration so that for the childs own identity card program currently the emphasis was on online media and the service went directly to the community. The process of achieving a communication strategy can be said to be good even though it is still not evenly distributed as a whole in the district of Bogor because there are still people who do not know the socialization carried out and are aware of the importance of the Child Identity Card program.